UNDERSTANDING SOIL CONSERVATION DECISION OF FARMERS IN THE GEDEB WATERSHED, ETHIOPIA. (14th January 2013) - Tesfaye, A.; Negatu, W.; Brouwer, R.; van der, P.; Fleskens, Luuk; Stringer, Lindsay C.
ABSTRACT The aim of this study was to investigate the main factors that influence smallholders' adoption decision of soil conservation measures in the Gedeb watershed. Data from 498 household heads who live in the three districts of the watershed were analysed using the binary logistic regression model. We find that farmers need adequate cash to invest in soil conservation measures. Moreover, farmers would be more encouraged to implement soil conservation measures when they have larger areas of cropland. We explore the possibility that when farmers presume that they have fertile land, they exploit their land more. This hints at the need for extension advice about the benefit of sustainable use of farmers' cropland so that they can maintain their land and pass it on to the future generation. Farmers' awareness about the benefit of land management practices and recognition of the problem erosion is causing on their crop land are central to their decision to adopt soil conservation measures. Furthermore, to adopt these measures, farmers have to be convinced about the effectiveness of these measures. Thus, awareness creation and demonstration of the effectiveness of these measures is essential. Because of the transboundary nature of the problem, policy makers in downstream countries that are suffering from the off‐site impact (e.g. Sudan) would benefit from the information provided and support efforts in the implementation of soil conservation measures. Copyright © 2013 John Wiley & Sons, Ltd.